Multifractal investigation of Ag/DLC nanocomposite thin films - Ştefan Ţălu (Nature Portfolio, 2020)
Abstract The objective of this study is the experimental investigation of the silver in diamond-like carbon (Ag/DLC) nanocomposite prepared by the co-deposition of radio frequency plasma-enhanced chemical vapor deposition (RF-PECVD) and RF-sputtering. Atomic force microscopy (AFM), X-ray diffraction analyses, ultraviolet–visible (UV–visible) spectroscopy measurements were applied to describe the three-dimensional surface texture data in connection with the statistical, and multifractal analyses. Additional information about structure–property relationships in prepared Ag/DLC nanocomposite was studied in detail to allow a better understanding of the surface micromorphology. The performed analysis revealed the studied samples have multifractal properties and can be included in novel algorithms for graphical representation of complex geometrical shapes and implemented in computer simulation algorithms.